Hemi-Chorea and Brainstem Glioma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
A case-report from Baroda Medical College, India, concerns a 9-year-old girl who complained of difficulty in walking and involuntary movements of the left upper and lower limbs.